Proposed Quality Control Based on Analysis Using Statistical Quality Control Method on Quail Egg Production - Ferdi Kurniawan; Fahriza Nurul Azizah (School of Industrial and System Engineering, Telkom University, 2022)
Quality is one of the factors that have an important role in providing satisfaction to consumers. Theproblem of quality is an issue that is often discussed in companies to design a strategy to maintain thecompany's position and improve the company's competitiveness in global competition with othercompanies. One of the efforts that can be done to maintain and improve quality is through statisticalquality control. UMKM Puyuh Kompas is one type of poultry farming business that has not implementedthe principles of quality control. The purpose of the study was to analyze quality control in quail eggproduction, identify the types of defects in quail egg production, and provide suggestions for controllingthe types of defects in quail egg production in the UMKM. The research method used is statistical qualitycontrol method and the sampling technique used is purposive sample. The results showed that the qualitycontrol of the quail egg production process in the company had not been running well. The dominant typesof defects that occur in the production process are cracked eggs and pale eggs. Suggested actions that canbe taken to prevent and reduce disability levels are by setting standard operating procedures, improving thedesign and layout of the cage, and installing supporting components that can prevent quail from beingexposed to disease outbreaks and pest attacks.